An in vitro Model of Human Retinal Detachment Reveals Successive Death Pathway Activations - Potic, Jelena; Mbefo, Martial; Berger, Adeline; Nicolas, Michael; Wanner, Dana; Kostic, Corinne; Matet, Alexandre; Behar-Cohen, Francine; Moulin, Alexandre; Arsenijevic, Yvan (Frontiers in Neuroscience, 2020)
Purpose was to create an in vitro model of human retinal detachment (RD) to study the mechanisms of photoreceptor death. Methods: Human retinas were obtained through eye globe donations for research purposes and cultivated as explants. Cell death was investigated in retinas with (control) and without retinal pigment epithelium (RPE) cells to mimic RD. Tissues were studied at different time points and immunohistological analyses for TUNEL, Cleaved caspase3, AIF, CDK4 and the epigenetic mark H3K27me3 expressions were performed. Human and monkey eye globes with retinal detachment served as controls. Results: The number of TUNEL-positive cells, compared between 24h and 7 days, increased with time in both retinas with RPE (from 1.2 ± 0.46 to 8 ± 0.89, n=4) and without RPE (from 2.6 ± 0.73 to 16.3 ± 1.27, P<0.014). In the group without RPE, cell death peaked at day 3 (P=0.014) and was high until day 7. Almost no Cleaved caspase3 signal was observed, whereas a transient augmentation at day 3 of AIF-positive cells was observed to be about 10-fold in comparison to the control group (n=2). Few CDK4-positive cells were found in both groups, but significantly more in the RD group at day 7 (1.8±0.24 vs. 4.7±0.58, p=0.014). The H3K27me3 mark increased by 7-fold after 5 days in the RD group (p=0.014) and slightly decreased at day 7 and was also observed to be markedly increased in detached human and monkey retina samples. Conclusions: AIF expression coincides with the first peak of cell death, whereas the H3K27me3 mark increases during the cell death plateau, suggesting that photoreceptor death is induced by different successive pathways after RD. This in vitro model should permit the identification of neuroprotective drugs with clinical relevance.